Models of T cell antigen receptor activation: the puzzle still remained - Deswal, Sumit (Nepal Journal of Biotechnology, 2012)
T cell antigen receptor (TCR) is a protein-complex expressed on all T cells of the immune system and is responsible for the activation of T cells when infectious agent is presented by an antigen presenting cell (APC) in the form of peptides bound to the major histocompatibility complex (pMHC). Despite numerous studies it is not clear what biochemical changes upon binding of antigen ligand to the extracellular domains of TCR leads to activation of intracellular signaling (a process known as TCR triggering). This review summarizes possible biochemical mechanisms for TCR triggering and discusses their comparative limitations and advantages in explaining various experimental observations.Keywords: T cell antigen receptor; activation; modelDOI: http://dx.doi.org/10.3126/njb.v2i1.5684Nepal Journal of Biotechnology Jan.2012, Vol.2(1): 62-71